SYSTEMATIC LITERATUR REVIEW: SYNTHESIS OF SILVER NANOPARTICLES (AgNPs) USING SECONDARY METABOLITES OF FRUIT PEEL EXTRACT - Indana Lazulfa; Erindyah Retno Wikantyasning (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
The synthesis of silver nanoparticles (AgNPs) using secondary metabolites of biological materials is a simple, cost-effective, and environmentally friendly method compared to physical synthesis methods. The secondary metabolites of the fruit peel extract can be used to synthesize AgNPs. Researchers chose experimental research articles with the theme of silver nanoparticle synthesis using fruit peels for review and selected journals published from 2018 to 2022 from web searches PubMed, Google Schoolar, Scopus, and ScienceDirect. The researchers screened and selected 28 articles according to the inclusion and exclusion criteria. The synthesis of AgNPs using fruit peel extracts can produce stable nanosized AgNPs. Silver nanoparticles synthesized using fruit peels showed stable silver nanoparticle synthesis results in terms of zeta potential and polydispersity index (PDI) values and obtained an average size of 2–200 nm with a spherical shape. Keywords: Silver Nanoparticles, Fruit Peel Extract, Antibacterial agent